Unveiling student perspectives on online presentations - Siti Ainun Jariyah, Hassan; Hamizah, Zahari; Ezihaslinda, Ngah (UPM, 2024)
Online presentations have become an integral part of academic settings, especially with the rise of digital education and remote learning. In a typical online presentation, students deliver information or projects through digital platforms, sharing their work in real time with instructors and peers. Various tools, such as Zoom, Microsoft Teams, and Google Meet, are frequently used to facilitate these presentations. These platforms support features like screen sharing, video recording, and audience interaction, making them versatile for educational purposes.